Chikungunya Virus in Macaques, Malaysia - Sam, I-Ching; Chua, Chong Long; Rovie-Ryan, Jeffrine J.; Fu, Jolene Y.L.; Tong, Charmaine; Sitam, Frankie Thomas; Chan, Yoke Fun (Centers for Disease Control and Prevention, 2015)
In the past 10 years, chikungunya virus (CHIKV) has caused global epidemics of fever, rash, and arthralgia affecting millions of humans, most recently in the Americas (1). CHIKV is an alphavirus transmitted by Aedes spp. mosquitoes. This virus has been isolated from wild vertebrates, particularly nonhuman primates (NHPs), in Africa (2). This sylvatic cycle might maintain the virus during interepidemic periods. The role of sylvatic cycles in Asia is less clear.